Role of Oxidative Stress in the Development of Cardiac Depression in Severe Isolated Brain Injury (Experimental Study) - V. V. Rusakov; V. T. Dolgikh; V. I. Chesnokov; N. N. Solodnikov (Общая реаниматология, 2009)
Objective: to study the role of oxidative stress in the development of cardiac structural and metabolic disorders in severe isolated brain injury (BI). Materials and methods. The impact of BI on the parameters of serum chemilu-minescence and the contractility of isolated rat hearts were studied in experiments on 66 outbred male albino rats, as described by E. T. Fallen et al. Lipid peroxidation processes were inhibited, by intraperitoneally injecting the antioxidant carnosine (100 mg/kg) 1 and 24 hours before or just after BI. Results. The rate of free radical processes rose an hour after severe isolated BI, which was associated with the indirect signs of cardiomyocitic membrane damages, depressed rat heart contractility, and their diminished resistance to hypoxia, reoxygenation, and exercise by high rhythm. Administration of carnosine to the animals favored the normalization of chemluminescent values with the high overall antioxidative capacity of serum. The effect of the agent depended on the time of its use and it was high when carnosine was injected 1 and 24 hours before injury. At the stage of reoxygenation after the hypoxic test, there was a significant increase in evolving pressure, the rate of left ventricular myocardial contraction and relaxation, and a reduction in AsAT activity in all coronary duct tests, as compared with the controls. A negative correlation was found between the burst amplitude and the myocardial relaxation rate in the animals receiving the agent. Conclusion. Improved cardiac contractility and increased capacities of the mechanisms responsible for Ca2+ transport due to the use of the antioxidant carnosine allow one to state that oxidative stress is one of the pathogenetic factors of cardiac depression in severe isolated BI. Key words: brain injury, heart, oxidative stress, carnosine.